The Relationship between Learning Styles and Use of Information and Communication Technologies in Adult Education - Lorena Acosta-Castillo (Universidad Nacional, Costa Rica, 2016)
This research aimed to identify the learning styles and the strategies used by adult students to involve ICTs in their knowledge. To achieve this, a qualitative research approach was carried out. The participants were members of the community who participated in a project called "Literacy in the Information Management of a University Corporation". The group consisted of 100 persons; their ages ranged between 40 and 59 years. The instruments used were the VARK inventory for learning styles, Observation and a field journal. The VARK inventory identified the learning styles used by adults. The Observation allowed the understanding of the environment or the context of these students, their relations with peers and with their teachers, and also to analyze the strategies used to develop topics through TICs integration. One of the main findings obtained was that 70% of the adult students have a multimodal learning style; for instance, they process knowledge in more than one way.